Benefits and limitations of the transfer online of Irish College of General Practitioners (ICGP) continuing medical education (CME) small group learning (SGL) during COVID-19: a national Delphi study - Stephanie Dowling; Finola Minihan; Claire McNicholas; Laoise Byrne; Pat Harrold; John Bourke; Walter Cullen; Gillian Doran (James Cook University, 2023)
Introduction: In Ireland, continuing medical education (CME) small group learning (SGL) has been shown to be an effective way of delivering CME, particularly for rural general practitioners (GPs). This study sought to determine the benefits and limitations of the relocation of this education from face to face to online learning during COVID-19. Methods: A Delphi survey method was used to obtain a consensus opinion from a group of GPs recruited via email through their respective CME tutors, and who had consented to participate. The first round gathered demographic details and asked doctors to report the benefits and/or limitations of learning online in their established Irish College of General Practitioners (ICGP) small groups. Results: A total of 88 GPs from 10 different geographical areas participated. Response rates in rounds one, two and three were 72%, 62.5% and 64%, respectively. The study group was 40% male; 70% were in practice ≥15 years, 20% practiced rurally, and 20% were single-handed. Attending established CME-SGL groups allowed GPs to discuss the practical application of rapidly changing guidelines both in COVID-19 and non-COVID-19 care. They could discuss new local services and compare their practice with others during a time of change; this helped them feel less isolated. They reported that online meetings were less social; moreover, the informal learning that occurs before and after meetings did not take place. Conclusion: GPs in established CME-SGL groups benefited from online learning as they could discuss how to adapt to rapidly changing guidelines while feeling supported and less isolated. They report that face to face meetings offer more opportunities for informal learning.